Pengaruh Mediasi Efesiensi Investasi pada Hubungan Corporate Governance dan Kinerja Keuangan BUMN di Indonesia Periode Sebelum Pandemi - Arif, Zalfa Khayliz Leviratna; Wafaretta, Vega (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2024)
Implementation of Corporate Governance (CG) is closely related to efficient investment decisions to drive financial performance, but several State-Owned Enterprises (SOEs) in Indonesia are indicated to have inefficient investments. This study aims to examine the impact of CG on financial performance, and the role of investment efficiency as a mediation between CG and financial performance. The sample comprises 10 SOEs listed on the Indonesia Stock Exchange for the 2013-2019 period since the publication of the SOE regulations regarding CG assessment indicators in 2012. The analysis method uses panel data regression analysis. The results of the study found that the CG index reduced financial performance and the level of investment efficiency. These results do not confirm the resource-based theory because a high CG score results in inefficient investment (over/under investment) and lowers financial performance. In addition, investment efficiency is not able to mediate the effect of CG on financial performance due to the different industrial sectors in the sample having different investment needs. The implication of this research is the need to expand investment space for companies as well as monitor to implement various management policies by the Ministry of SOEs